Acting out: a mistake and an opportunity - García, Lucía Natalí (2024)
This paper presents a theoretical review of the concept of acting out in psychoanalysis from the perspective of the French school. The aim is to explore how this phenomenon, which involves the expression of unconscious conflicts through actions, can be leveraged as a therapeutic opportunity rather than simply an obstacle. Through two clinical scenes, it is illustrated how acting out can reveal unconscious aspects of the patient and signal interpretative errors by the analyst. Appropriate interventions to address acting out are discussed, highlighting its nature as a demand for symbolization in the transference. In conclusion, the importance of understanding and managing acting out within the transference as a tool for therapeutic development is emphasized, together with the need for careful supervision of the transference relationship to optimize its transformative potential.